2010
DOI: 10.1007/978-3-642-13443-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Methylxanthines and Reproduction

Abstract: Reproduction is the process by which organisms create descendants. In human reproduction, two kinds of sex cells, or gametes, are involved. Sperm, the male gamete, and egg egg , or ovum ovum Vedi egg , the female gamete, must meet in the female reproductive system to create a new individual and both the female and the male reproductive systems are essential to the occurrence of reproduction. Scientific reports dealing with the effects of methylxanthines on reproduction are mostly centred on the use of these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 119 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…Caffeine, the most widely consumed methylxanthine, can act as a non‐selective adenosine antagonist within the human body and therefore increase the intracellular concentration of cAMP and induce an increase in catecholamine excretion in the mother and fetus, which may lead to uteroplacental vasoconstriction and hypoxia. 32 , 42 , 43 , 44 In addition, it was reported that caffeine may alter circulating levels of luteal estrogens and sex hormone‐binding globulin, suggesting that caffeine may exert a potential detrimental effect on the reproductive system by affecting the hypothalamic–pituitary–gonadal axis. 45 However, the results were inconsistent and detailed mechanisms or pathways are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine, the most widely consumed methylxanthine, can act as a non‐selective adenosine antagonist within the human body and therefore increase the intracellular concentration of cAMP and induce an increase in catecholamine excretion in the mother and fetus, which may lead to uteroplacental vasoconstriction and hypoxia. 32 , 42 , 43 , 44 In addition, it was reported that caffeine may alter circulating levels of luteal estrogens and sex hormone‐binding globulin, suggesting that caffeine may exert a potential detrimental effect on the reproductive system by affecting the hypothalamic–pituitary–gonadal axis. 45 However, the results were inconsistent and detailed mechanisms or pathways are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be explained by differences in the organization of the ER or by the lower sensitivity of ryanodine receptors in this species. In addition, it was reported that caffeine may modify the activity of phosphodiesterase to induce an increase in cAMP levels (Kren et al ., 2004; Mishra & Joy, 2006; Minelli & Bellezza, 2011) that could inhibit meiosis resumption. Our experiments cannot rule out the possibility that the inhibitory effect of cAMP may be more important than the stimulatory effect of the Ca 2+ released by RyR activation.…”
Section: Discussionmentioning
confidence: 99%
“…In all female animals of the treated and control groups, the histology of the ovaries, uterus, and vagina were normal. E ects on spermatogenesis (and testicular atrophy) are well known with respect to the methylxanthines, and have been observed in rats, rabbits, and roosters and are generally thought to be reversible up on cessation of treatment [34]. Gans, observed these e ects in ca eine-and theobromine-treated rats [32] while Weinberger et al also observed them at high dietary doses in ca eine-, theobromine-, and theophylline-treated rats [35].…”
Section: Organ Weightsmentioning
confidence: 99%
“…Gans, observed these e ects in ca eine-and theobromine-treated rats [32] while Weinberger et al also observed them at high dietary doses in ca eine-, theobromine-, and theophylline-treated rats [35]. ese e ects, at least with respect to ca eine, have been largely attributed to suppression of follicle-stimulating hormone [34]. Testicular atrophy and inhibition of spermatogenesis have also been observed in rats treated with theacrine.…”
Section: Organ Weightsmentioning
confidence: 99%